Macroporous biohybrid cryogels for co-housing pancreatic islets with mesenchymal stromal cells. (15th October 2016) - Borg, Danielle J.; Welzel, Petra B.; Grimmer, Milauscha; Friedrichs, Jens; Weigelt, Marc; Wilhelm, Carmen; Prewitz, Marina; Stißel, Aline; Hommel, Angela; Kurth, Thomas; Freudenberg, Uwe; Bonifacio, Ezio; et al.
Graphical abstract: Abstract: Intrahepatic transplantation of allogeneic pancreatic islets offers a promising therapy for type 1 diabetes. However, long-term insulin independency is often not achieved due to severe islet loss shortly after transplantation. To improve islet survival and function, extrahepatic biomaterial-assisted transplantation of pancreatic islets to alternative sites has been suggested. Herein, we present macroporous, star-shaped poly(ethylene glycol) (starPEG)-heparin cryogel scaffolds, covalently modified with adhesion peptides, for the housing of pancreatic islets in three-dimensional (3D) co-culture with adherent mesenchymal stromal cells (MSC) as accessory cells. The implantable biohybrid scaffolds provide efficient transport properties, mechanical protection, and a supportive extracellular environment as a desirable niche for the islets. MSC colonized the cryogel scaffolds and produced extracellular matrix proteins that are important components of the natural islet microenvironment known to facilitate matrix-cell interactions and to prevent cellular stress. Islets survived the seeding procedure into the cryogel scaffolds and secreted insulin after glucose stimulation in vitro . In a rodent model, intact islets and MSC could be visualized within the scaffolds seven days after subcutaneous transplantation. Overall, this demonstrates the potential of customized macroporous starPEG-heparin cryogel scaffolds in combination with MSC to serve as a multifunctional islet supportive carrier for transplantation applications. Statement of Significance: Diabetes results in the insufficient production of insulin by the pancreatic β-cells in the islets of Langerhans. Transplantation of pancreatic islets offers valuable options for treating the disease; however, many transplanted islets often do not survive the transplantation or die shortly thereafter. Co-transplanted, supporting cells and biomaterials can be instrumental for improving islet survival, function and protection from the immune system. In the present study, islet supportive hydrogel sponges were explored for the co-transplantation of islets and mesenchymal stromal cells. Survival and continued function of the supported islets were demonstrated in vitro . The in vivo feasibility of the approach was shown by transplantation in a mouse model.